TMPRSS2-ERG fusion promotes prostate cancer metastases in bone - Deplus, Rachel (Oncotarget, 2016)
Bone metastasis is the major deleterious event in prostate cancer (PCa). TMPRSS2-ERG fusion is one of the most common chromosomic rearrangements in PCa. However, its implication in bone metastasis development is still unclear. Since bone metastasis starts with the tropism of cancer cells to bone through specific migratory and invasive processes involving osteomimetic capabilities, it is crucial to better our understanding of the influence of TMPRSS2-ERG expression in the mechanisms underlying the bone tropism properties of PCa cells. We developed bioluminescent cell lines expressing the TMPRSS2-ERG fusion in order to assess its role in tumor growth and bone metastasis appearance in a mouse model. First, we showed that the TMPRSS2-ERG fusion increases cell migration and subcutaneous tumor size. Second, using intracardiac injection experiments in mice, we showed that the expression of TMPRSS2-ERG fusion increases the number of metastases in bone. Moreover, TMPRSS2-ERG affects the pattern of metastatic spread by increasing the incidence of tumors in hind limbs and spine, which are two of the most frequent sites of human PCa metastases. Finally, transcriptome analysis highlighted a series of genes regulated by the fusion and involved in the metastatic process. Altogether, our work indicates that TMPRSS2-ERG increases bone tropism of PCa cells and metastasis development.